Diversity and special education in dialogues: reflections about the inclusion discourse - Antônio Carlos do Nascimento Osório; Tatiana Calheiros Lapas Leão (Universidade Federal de Santa Maria (UFSM), 2013)
This article addresses issues related to production of discourses on inclusion of special education students within the schooling process in regular schools. The theoretical and methodological framework is based on references of Michel Foucault and his epistemological possibilities of understanding as a problematization surrounded by a social issue about inclusion possibilities. For Foucault (1975), valuing diversity is enmeshed in the formation of the concept of abnormality, with the principles of truth and justice, in the grotesque exercise of the mechanics of power, knowledge concerning a subject seen as different. The objective in this discussion is to do a reflection on some files which preceded the orientation of subsidies of the document produced as National Policy on Special Education. In this reflection, under the inclusion perspective, their possibilities and limits of transgression are demonstrated together, making it clear that this is not limited to the aspects relating to teaching practices and, but to social practices marked by an arsenal of prejudices. The results revealed that, nowadays, the discourse on school inclusion in these files bring the exam as a strategy for agglutination, allowing a better control of the differences and that the schools that have not been able to care for those students considered normal are now responsible for this social correction. Such conditions create a variety of different challenges to school structure, results from accumulated distortions by the deviation of these purposes, as field of conflicts and strengthening of social differences.